Inventarisasi Jenis Serangga Pada Budidaya Edamame (Glycine max L. Merr.) - Musyarrofah, Musyarrofah; Nurlaila, Nurlaila; Ellya, Hikma (Universitas Lambung Mangkurat, 2025)
Edamame (Glycine max L.) is a type of plant that is included in the vegetable category. Edamame soybeans have a relatively high nutritional content, where every 100 grams of seeds contain protein, carbohydrates, fat, vitamin A or carotene, vitamin B3, vitamin B2, vitamin B1, vitamin C, as well as minerals such as phosphorus, calcium, iron and potassium. Edamame plants are one of the plants that can be attacked by pests from the time they start growing until just before harvest. In Indonesia, more than 111 arthropod species are recorded as pests, 53 species are non-target, 61 species are predators and 41 species are parasitoids. There are 17 types of pests recorded that can cause damage and loss to soybean plants. Some of the main pests that are often found are bean flies (Spodoptera litura), (Ophiomyia phaseoli), armyworms tuber leaf beetles (Phaedonia inclusa), pod suckers (Riptortus linearis), pod borers (Etiella zinckenella), and green ladybugs (Nezara viridula) . Fertilizer is an additional material given to the soil with the aim of enriching or improving the chemical, physical and biological conditions of soil fertility This research aims to determine the diversity of insect pests in edamame cultivation given different doses of livestock manure bokashi fertilizer. This research was carried out from July 2023 to November 2023, located in the Khalid Waste Bank Area RT 5/ RW 5, Guntung Paikat Village, Banjarbaru. This research used a Randomized Block Design method to identify the types of insects found in edamame cultivation where bokashi fertilizer was applied.